The Importance of Maintaining Long-Term Sustainability of Public Finances (Acta Universitatis Danubius. Œconomica, 2024)
This paper aims highlighting the importance of maintaining long-term sustainability of public finances through the continuation of measures for economic recovery, accelerating economic growth, and maintaining and supporting a new framework for sustainable development that leads to the elimination of vulnerabilities in the economy and ensures a decent standard of living. The main objectives for creating and consolidating public finances aim at improving the quality of public spending by improving budget planning, implementing reforms in the labor, pension, and SME support sectors, prioritizing sectoral policies, ensuring real competition between proposed projects for funding, and supporting performance by using the best practices at the European level and avoiding wastage of public funds. The paper analyzes the degree of fiscal consolidation achieved, contributing to reducing inflation, interest rates, the trade deficit, and the current account deficit of the balance of payments, as well as the stability of the leu exchange rate, taking into account the fragility of the domestic and external environment, the budgetary effort required for the new pension system law, and the implementation of reforms from the PNRR, which must be completed by 2026. Considering the issues mentioned above, Romania has set several objectives to ensure the sustainability of the gross financing needs, such as reducing the budget deficit by supporting and adapting the business environment to the challenges posed by economic crises, simplifying taxation, and improving legislation to address tax evasion, to create the conditions for healthy and sustainable economic growth.